2009
DOI: 10.1016/j.urolonc.2007.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Failure to achieve a complete response to induction BCG therapy is associated with increased risk of disease worsening and death in patients with high risk non-muscle invasive bladder cancer

Abstract: Purpose-The Southwest Oncology Group conducted a randomized trial of induction BCG with or without maintenance BCG. In these additional retrospective analyses, our goal was to evaluate the association of a complete response (CR) or remaining with no evidence of disease (NED) versus no CR during induction therapy with subsequent survival after adjusting for other potential confounders. Among all patients randomized to maintenance treatment, we also wanted to identify combinations of baseline covariates in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 25 publications
(22 reference statements)
0
40
1
Order By: Relevance
“…Recurrence with papillary tumor(s) by 3 mo after induction of BCG is a poor prognostic indicator in patients with high-risk nonmuscle invasive bladder cancer [5,6], with a progression rate of 47% in those with clinical T1 (cT1) disease [7]. However, the impact of a clinical Ta (cTa) papillary recurrence at 3 mo after BCG is often debated.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence with papillary tumor(s) by 3 mo after induction of BCG is a poor prognostic indicator in patients with high-risk nonmuscle invasive bladder cancer [5,6], with a progression rate of 47% in those with clinical T1 (cT1) disease [7]. However, the impact of a clinical Ta (cTa) papillary recurrence at 3 mo after BCG is often debated.…”
Section: Introductionmentioning
confidence: 99%
“…Intravesical BCG provides a significant improvement in recurrence-free survival and consistently affords an improvement over intravesical chemotherapy. Unfortunately, up to 70% of patients with high-risk NMIBC will eventually recur despite intravesical BCG and some recurrent tumors will progress to higher stage (3, 4). …”
Section: Introductionmentioning
confidence: 99%
“…RC also seems to be one of the options for selected patients with a diagnosis of high-risk non-muscle-invasive bladder cancer because it was shown that it brings significant survival benefit when compared with patients having RC at the time of progression into muscle-invasive disease [3,4,5,6]. It may be even more important in some patients with previous bacillus Calmette-Guérin treatment failure; it was shown that in general this group of patients is at increased risk of death from disease progression [7]. Nevertheless, early RC is performed in only 4.7-8% of patients with high-risk non-muscle-invasive bladder cancer as it carries non-negligible risks of surgical complications and a major impact on quality of life (QoL) following surgery, depending on the type of urinary diversion [3,8].…”
Section: Introductionmentioning
confidence: 99%